Review of N. Piers Ludlow, Roy Jenkins and the European Commission Presidency, 1976-1980: At the Heart of Europe - Malcolm Craig (Journal of Contemporary European Research, 2017)
A fine piece of research and writing on a pivotal figure in British and European political history. Using previously untouched archives, this work on Roy Jenkins and his period as president of the European Commission is a valuable addition to the scholarship on Britain’s storied relationship with the European project.